Studying the relationship between higher education outcomes and the unemployed according to the educational situation in Syria using legal link - درويش رامي; أحمد طالب (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to analyze the relationship between higher education outcomes and the unemployed according to the educational situation in Syria during the period 2000-2018, and to build mathematical models that represent this relationship using the legal link method.The most important results were: There is a statistically significant relationship between graduates of higher education and the unemployed according to the educational status, and this relationship can be represented by two legal variables. The variable of graduates of public universities is the most closely related to the first legal variable, and graduates of technical institutes is the most closely related to the second legal variable. The first legal variable is strongly correlated with the unemployed who hold a secondary certificate, and the second legal variable is strongly correlated with the unemployed who hold a preparatory certificate.